VD_FINDINFO Jug / 2024 / 42 vom 20. Juli 2023 - VD Tribunal cantonal (2023)
VOLDROIT PÉNAL, INFRACTION D'IMPORTANCE MINEURE, CONCOURS D'INFRACTIONS, REJET DE LA DEMANDE | 139 ch. 1 CP, 172ter CP, 10 CPP (CH)